CAPTURE RESULTS OF BABY LOBSTERS (Panulirus sp.) LANDED FROM PACITAN COASTAL WATERS - Andriyono, Sapto; Wijanarko, Puguh Yugo; Mahasri, Gunanti; Saroso, Heri (Journal of Aquatropica Asia, 2025)
Lobsters from the Panulirus sp. group are a potential resource in renewable fisheries, but when exploitation continues to increase and there is no control, the number may continue to decline and become extinct. Lobster catching is not limited to the adult phase, but in all phases, including the puerulus phase (baby lobster/clear lobster seed). This study aimed to determine the diversity of baby lobster seeds landed in coastal waters in the Pacitan Regency area based on baby lobster catching activities. This research was conducted in January 2023 - January 2024. Data processing using Primer7 and MS Excel software. Based on the results of observations and data collection, both primary and secondary, 4 lobster species were obtained, namely pearl lobster (Panulirus ornatus), sand lobster (Panulirus homarus), bamboo lobster (Panulirus versicolor), and batik lobster (Panulirus longipes). Sand lobster, pearl lobster, batik lobster, and bamboo lobster were the most abundant at each station. During sampling, the average value of monthly catches in 2024 decreased compared to 2023. Water quality in this area is suitable for lobster habitat, with DO 8-8.5 ppm, salinity 33-35 ppt, pH 7-7.2, and temperature 27.0- 29.2 °C.